KOMPOSISI KUMBANG TINJA (DUNG BEETLES) DI PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq.) RAKYAT DI KANAGARIAN KUNANGAN PARIK RANTANG KABUPATEN SIJUNJUNG - Wati, Tri Ambar; Dahelmi, Dahelmi; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACT Dung Beetles is group member of Coleoptera that known as Scarab beetles. Dung Beetles have important role in ecosystem as biological control. This study was conducted from March to May 2013 at Oil Palm Plantation, Parik Rantang, Sijunjung District. The aim of this study is to know dung beetles composition and abiotic factor in Oil Palm Plantation (Elaeis guineensis Jacq.). This study was done by using Pitfall Traps/ Dung Traps method. In this study, four species of dung beetle that belonging to one genus (Onthophagus) and one subfamily (Scarabaeineae). The number of dung beetle was high in Onthophagus seniculus (280 individuals) and low in Onthophagus australis (5 individuals). Mean density relative and relative frequency were higher in Onthophagus seniculus (67,4% and 37,2%) and which lower is Onthophagus australis (1,6% and 7,4%). Soiltemperature, air temperature, soil water content and air humidity were 23,90C,23,4% and 55,3%, respectively.